Partogram: an important tool in managing labour! - Mukherjee, Swagatha; M., Raksha; V., Malini K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Various types and designs of partographs are being used at various centers. WHO introduced simplified version of partogram, for the use by skilled birth attendant. Preprinted paper versions of the partograph are available Methods: 100 antenatal women were selected for study. Patients with vertex presentation and singleton pregnancy were taken. Patients who came late in labour and those with cephalopelvic disproportion were not included in the study. Cervical Dilatation in cms was assessed by per vaginal examination every 2 hourly, fetal Heart Rate every ½ hourly, uterine contractions and maternal pulse measured every ½ hourly, maternal BP and temperature were measured every 4th hourly. Results: Using WHO simplified partogram, characteristics of labour and neonatal outcome was evaluated. Among the 100 women included in the study, 78 required augmentation of labour, here 6 of them crossed the alert line and underwent LSCS. Of the 22 women who did not require augmentation, 4 crossed the alert line and underwent LSCS. We didn’t find any difference in monitoring of labour using simplified version of WHO partogram compared with other partograms, apparently it’s more simpler to plot and easy to understand. Conclusions: An alert line on partogram should be based on lower 10th centile rate of cervical dilatation of the local population. We found this rate as 1cm/hr, which corresponds to the slope of alert line on standard partogram. Based on this we conclude, simplified partogram is good enough for monitoring labour progress.